Regulatory competition and cross‐fertilization in bank performance in the US banking markets - Tirtiroglu, Dogan; Tanyeri‐Günsür, Basak; Tirtiroglu, Ercan (Financial markets, institutions & instruments, 2024)
This paper examines empirically cross‐fertilization in the productivity growth of banks between a state and its neighbouring and non‐neighbouring states (i) before (i.e. 1971–1977) the interstate multibank holding company (IMBHC) deregulations and (ii) during (i.e. 1982–1995) the IMBHC deregulations, which, through cross‐border bank M&As mainly among neighbouring states, could inject new blood, awaken the market for corporate control and enhance cross‐fertilization in bank performance among neighbouring states. Further, the 1978–1981 period offers a natural experiment to examine Baumol's Contestable Markets Hypothesis (CMH). The legislature of Maine made the first IMBHC deregulatory move in 1978. There was no reciprocity until New York and Alaska made their moves in 1982. Under CMH, Maine's move should inject a competitive spirit and alter bank performance for better across all—neighbouring or non‐neighbouring – banking markets during this period. Theoretically, Kane's regulatory equilibrium framework provides guidance to address these matters and Tiebout's people vote with their feet framework extends and supplements this guidance. Empirically, FDIC's annual banking data, aggregated at the state level, constitute the main input in computing the productivity growth indices for each of the 48 contiguous sample states between 1971 and 1995. Estimations of a novel spatially driven fixed effects model that uses these indices produce empirical results. The empirical model exploits the proximity of one sample state to its neighbouring states while also embracing a set of randomly chosen non‐neighbouring states as a control sample. Results show that cross‐fertilization in bank performance, observed among neighbouring states before the introduction of the IMBHC deregulations during 1971–1977, gets stronger in response to the dynamically evolving IMBHC deregulations during 1982–1995 and that improvements in banks' productivity growth during 1978–1981 support Baumol's CMH. Overall, our results demonstrate the importance and influence of cross‐fertilization, as a matter of proximity of subjects, on banks' performance and suggest promise for future research that embraces the spatial dimension of banking markets and data.